Low-carbon pathways to digitalization: can the digital economy improve carbon efficiency? - Yuan, Shuaifeng; Zhang, Xiaoyang; Liu, Shiliang; Li, Zhihui (Frontiers in Environmental Science, 2025)
IntroductionThis study investigates the impact of the digital economy on the carbon emission efficiency of 282 prefecture-level cities in China from 2008 to 2020.MethodsThis study used two-way fixed panel model, moderated effects model, CCR-SBM model and spatial Durbin model.ResultsThere is an obvious “U”-shaped relationship between the digital economy and carbon emission efficiency, with a linear coefficient of −0.320. In addition, the Dig data shows a substantial inflection point at 2.62, thus confirming the obvious correlation between the digital economy and carbon emission efficiency. After conducting a series of robustness tests (including endogeneity tests and alternative model specifications), the model was found to show consistent positive correlation. The results of the mechanism tests suggest that human capital reinforces the positive impact of the digital economy on carbon emission efficiency by accelerating the inflection point of the U-curve. In addition, the digital economy has been shown to enhance carbon emission efficiency through industrial structural transformation and marketization. Heterogeneity analysis shows that regional location, city size and characteristics influence this effect.DiscussionThe results of the study, provide insights into the green, low-carbon and high-quality development of Chinese cities.